Letters from Hollywood inside the private world of classic American moviemaking - Lang, Rocky ca. 2, H. 20. Jh./Anfang 21. Jh; Lang, Rocky ca. 2, H. 20. Jh./Anfang 21. Jh; Hall, Barbara 1961-; Hall, Barbara 1961-; Bogdanovich, Peter 1939-2022 (Abrams, 2019)
"A collection unlike any other, Letters from Hollywood reproduces rare correspondence between some of the most notable and talented film industry names of all time--from the silent era to the Golden Age and up through the pre-email days of the 1970s. Culled from university libraries, archives, and personal collections, by filmmaker Rocky Lang and archivist Barbara Hall, this is the first time most of these letters, memos, and telegrams have been printed in full, with many having never been seen by the greater public until now. Organized chronologically, each note is thoughtfully annotated by the authors to provide inside into the private world of its writer and recipient. Comprised of intimate messages exchanged between colleagues, friends, lovers, and rivals, Letters from Hollywood captures the larger-than-life personalities and behind-the-scenes practices that would define the industry for years to come. This star-studded compendium also celebrates the lost art of letter writing--the romance and excitement of a personal typewritten or hand-scrawled message sealed and sent. Letters from Hollywood's extensive roster of contributors include movie legends like Greta Garbo, Alfred Hitchcock, Katharine Hepburn, Marlon Brando, Elia Kazan, Cary Grant, Francis Ford Coppola, Tom Hanks, and more. Their letters offer all the intrigue and glamour of early Hollywood, and together they form a fascinating picture of a bygone, though not forgotten, era in America moviemaking"--Dust jacket flap
Includes index
Rare notes, memos, and telgrams from Humphrey Bogart, Audrey Hepburn, Frank Sinatra, Jand Fonda, and more -- (Cover)
Keywords: Actors / Correspondence; Motion picture actors and actresses / Correspondence; American letters / California / Los Angeles; Motion picture industry / California / Los Angeles; Hollywood (Los Angeles, Calif.); Acteurs / Correspondance; Lettres américaines (Genre littéraire) / Californie / Los Angeles; Cinéma / Industrie / Californie / Los Angeles; Actors; American letters; Motion picture actors and actresses; Motion picture industry; California / Los Angeles; California / Los Angeles / Hollywood; facsimiles (reproductions); Facsimiles; Personal correspondence; Correspondance privée; Fac-similés